2015
DOI: 10.1088/0953-4075/48/16/164005
|View full text |Cite
|
Sign up to set email alerts
|

A theoretical study of the dynamics of paramagnetic superrotors in external magnetic fields

Abstract: We present a detailed theoretical study of oxygen molecules in high rotational states (molecular superrotors) interacting with an external magnetic field. The system shows rich dynamics, ranging from a spin-selective splitting of the angular distribution over molecular alignment to an inversion of the rotational direction. We find that the observed magneto-rotational effects are due to a spin-mediated precession of the orbital angular momentum around the magnetic field. Analytical expressions for the precessio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 51 publications
1
10
0
Order By: Relevance
“…Note that using Ω N,+1 = Ω N,−1 ≡ Ω N = µ B gB/( N ) in accord with Eq.2 did not produce satisfactory fits, owing to the partial decoupling of S from N at high values of magnetic field [22]. To account for this effect, we numerically diagonalized the spin-rotational Hamiltonian in the presence of an external magnetic field:…”
Section: Transverse Magnetizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Note that using Ω N,+1 = Ω N,−1 ≡ Ω N = µ B gB/( N ) in accord with Eq.2 did not produce satisfactory fits, owing to the partial decoupling of S from N at high values of magnetic field [22]. To account for this effect, we numerically diagonalized the spin-rotational Hamiltonian in the presence of an external magnetic field:…”
Section: Transverse Magnetizationmentioning
confidence: 99%
“…To study the induced magnetization further, we applied an external magnetic field along the vertical (ẑ) axis. In a recent study of the dynamics of paramagnetic oxygen super-rotors in an external magnetic field [21][22][23], it was found that the spin-rotation coupling serves as an efficient mediator between the applied B-field and the molecular rotation, enabling magnetic control of the rotational degree of freedom. Here, we demonstrate the effect of SR coupling on the centrifuge-induced magnetization.…”
Section: Non-zero External Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…Using J S, we approximated the angular distribution of the state |N, S, J, M J by the spherical harmonics Y J,M J (θ, φ). This approximation was verified by a more elaborate calculation of the exact angular distributions [31]. Using this approximation, the final angular distribution at time t is given as:…”
Section: Magneto-optical Properties Of Paramagnetic Super Rotorsmentioning
confidence: 84%
“…Consider a Hund's case (b) molecule possessing an electronic spin, such as molecular oxygen 16 O 2 in the ground electronic state. Its electronic spin is strongly coupled to the molecular angular momentum N. In an external magnetic field, sufficiently weak for not causing the spin to decouple from N, the angular momentum will precess with frequency [31]…”
Section: Dynamics Of Super Rotors In External Magnetic Fieldsmentioning
confidence: 99%